2018
DOI: 10.1029/2018jg004727
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Water and Carbon Fluxes to Constrain Estimates of Transpiration: The TEA Algorithm

Abstract: Plant transpiration (T), biologically controlled movement of water from soil to atmosphere, currently lacks sufficient estimates in space and time to characterize global ecohydrology. Here we describe the Transpiration Estimation Algorithm (TEA), which uses both the signals of gross primary productivity and evapotranspiration (ET) to estimate temporal patterns of water use efficiency (WUE, i.e., the ratio between gross primary productivity and T) from which T is calculated. The method first isolates periods wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 49 publications
2
100
0
Order By: Relevance
“…Also central to many E and T partitioning approaches is the notion that T/ET intermittently approaches 1 (Berkelhammer et al, 2016;Nelson et al, 2018;Zhou et al, 2016), as suggested by some modeling analyses (Wei et al, 2018). This assumption was critiqued by Perez-Priego et al (2018), who demonstrated that T/ET was rarely greater than 0.8 in a Mediterranean ecosystem, even during dry periods when surface soil moisture was less than 0.2 m 3 m -3 , and that E scaled with time -0.5 5 following (Brutsaert, 2014) [see also Boese et al (2018)].…”
Section: Does T/et Approach Unity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Also central to many E and T partitioning approaches is the notion that T/ET intermittently approaches 1 (Berkelhammer et al, 2016;Nelson et al, 2018;Zhou et al, 2016), as suggested by some modeling analyses (Wei et al, 2018). This assumption was critiqued by Perez-Priego et al (2018), who demonstrated that T/ET was rarely greater than 0.8 in a Mediterranean ecosystem, even during dry periods when surface soil moisture was less than 0.2 m 3 m -3 , and that E scaled with time -0.5 5 following (Brutsaert, 2014) [see also Boese et al (2018)].…”
Section: Does T/et Approach Unity?mentioning
confidence: 99%
“…et al (2018) andLi et al (2019) methods both circumvent the assumption that T/ET approaches unity at some periods by estimating ecosystem conductances. The Transpiration Estimation Algorithm (TEA) fromNelson et al (2018) utilizes a non-parametric model and thereby further limits assumptions made about how the ecosystem functions. However, 30…”
mentioning
confidence: 99%
“…Indirect in situ measurements of A n and T are based on the eddy covariance (EC) technique through flux partitioning of measured net ecosystem CO 2 fluxes (Reichstein et al, 2005) and water vapour fluxes (Nelson et al, 2018, Paul-Limoges et al, 2020, Scott & Biederman, 2017. The EC technique represents a vertically integrated canopy signal in high temporal resolution, but at a limited spatial extend (Baldocchi & Ryu, 2011).…”
mentioning
confidence: 99%
“…(10). Accurate knowledge of the isotope ratio within various water reservoirs of a landscape, including the planetary boundary layer (Noone et al, 2013), and how these translate into distinct water fluxes is required to advanced isotope-based partitioning approaches.…”
Section: Isotopic Approachesmentioning
confidence: 99%